Récit de voyage et tourisme de mémoire : The Island Martinique de John Wideman - Corinne Duboin (Études Caribéennes)
The African American writer John Edgar Wideman published in 2003 a travel memoir commissioned by the National Geographic Society. As an heir to a painful transatlantic History of colonialism, the writer chooses Martinique as his destination. Unfamiliar with this French-speaking Caribbean Island, Wideman transcribes his intimate experience of Martinique and guides his readers through a touristic and literary journey that becomes a reflection on the self in relation to others. Our analysis of Wideman’s travel writing aims to explore the author’s perception of the island as a touristic, historical, and cultural site.